Swc4 positively regulates telomere length independently of its roles in NuA4 and SWR1 complexes. Issue 22 (3rd December 2020) - Liu, Jia-Cheng; Li, Qian-Jin; He, Ming-Hong; Hu, Can; Dai, Pengfei; Meng, Fei-Long; Zhou, Bo O; Zhou, Jin-Qiu
Abstract: Telomeres at the ends of eukaryotic chromosomes are essential for genome integrality and stability. In order to identify genes that sustain telomere maintenance independently of telomerase recruitment, we have exploited the phenotype of over-long telomeres in the cells that express Cdc13-Est2 fusion protein, and examined 195 strains, in which individual non-essential gene deletion causes telomere shortening. We have identified 24 genes whose deletion results in dramatic failure of Cdc13-Est2 function, including those encoding components of telomerase, Yku, KEOPS and NMD complexes, as well as quite a few whose functions are not obvious in telomerase activity regulation. We have characterized Swc4, a shared subunit of histone acetyltransferase NuA4 and chromatin remodeling SWR1 (SWR1-C) complexes, in telomere length regulation. Deletion of SWC4, but not other non-essential subunits of either NuA4 or SWR1-C, causes significant telomere shortening. Consistently, simultaneous disassembly of NuA4 and SWR1-C does not affect telomere length. Interestingly, inactivation of Swc4 in telomerase null cells accelerates both telomere shortening and senescence rates. Swc4 associates with telomeric DNA in vivo, suggesting a direct role of Swc4 at telomeres. Taken together, our work reveals a distinct role of Swc4 in telomere length regulation, separable from its canonical roles in both NuA4 and SWR1-C.